Thermal charging study of compressed expanded natural graphite/phase change material composites. (November 2016) - Mallow, Anne; Abdelaziz, Omar; Graham, Samuel
Abstract: The thermal charging performance of paraffin wax combined with compressed expanded natural graphite foam was studied for different graphite bulk densities. Constant heat fluxes between 0.39 W/cm 2 and 1.55 W/cm 2 were applied, as well as a constant boundary temperature of 60 °C. Thermal charging experiments indicate that, in the design of thermal batteries, thermal conductivity of the composite alone is an insufficient metric to determine the influence of the graphite foam on the thermal energy storage. By dividing the latent heat of the composite by the time to end of melt for each applied boundary condition, the energy storage performance was calculated to show the effects of composite thermal conductivity, graphite bulk density, and latent heat capacity. For the experimental volume, the addition of graphite beyond a graphite bulk density of 100 kg/m 3 showed limited benefit on the energy storage performance due to the decrease in latent heat storage capacity. These experimental results are used to validate a numerical model to predict the time to melt and for future use in the design of heat exchangers with graphite-foam based phase change material composites. Size scale effects are explored parametrically with the validated model.